Retardant effect of sodium alginate on the retrogradation properties of normal cornstarch and anti-retrogradation mechanism. (August 2017) - Li, Qian-Qian; Wang, Yu-Sheng; Chen, Hai-Hua; Liu, Shuai; Li, Man
Abstract: The effect of sodium alginate (AG) on the retrogradation properties of normal cornstarch (NCS) and its anti-retrogradation mechanism were investigated by determining the pasting parameters, gel firmness, gelatinization parameters, retrogradation enthalpy, glass transition temperature, dynamic rheological properties, interaction force, leached amylose content, swelling power, X-ray diffraction patterns and relative crystallinity, respectively. The sodium alginate-normal cornstarch (AG-NCS) blends were treated with different ratio of NCS to AG (ranging from 10:0–9.6: 0.4) and stored at 4 °C and 25 °C for 1d or 3d, respectively. The addition of AG significantly decreased the setback value, which suggested that the short-term retrogradation of NCS was inhibited. AG obviously reduced the retrogradation enthalpy, storage modulus, and relative crystallinity of NCS, which decreased with the increase in the AG concentration. The aforementioned results suggested that addition of AG could retard the retrogradation of NCS, and the retardation effect exhibited positive correlation of AG concentration. The changes in the storage modulus after the addition of NaCl and urea suggested that the hydrogen bonding might be the main force involved in the formation and stability of the AG-NCS blends. The X-ray diffraction patterns showed that the transformation of the A-type to B-type of NCS occurred after gelatinization and retrogradation. Graphical abstract: Highlights: Sodium alginate exhibited a retardant effect on the retrogradation of normal cornstarch. The hydrogen bonding was the main force in the stability of AG-NCS blends. Starch exhibits a rapid retrogradation under 4 °C than that stored at 25 °C.